Comparison of Lithuanian, Italian and British Social Business Models - Zaneta Simanaviciene; Virgilijus Dirma; Larisa Kapranova; Dominyka Beniusyte; Arturas Simanavicius (Montenegrin Journal of Economics)
Daily life in the world is accompanied by a variety of global social problems such as discrimination, ignorance, suicides, poverty, hunger, environmental pollution and several others frequently caused by human beings. These have been particularly exacerbated by the recent and arguably ongoing economic crisis.